Diseño de un sistema fotovoltaico conectado a la red en el bloque b de la universidad técnica de Cotopaxi. - Potes Valencia, Paúl Wladimir (2019)
This research study quantified the amount of energy that a photovoltaic system connected to the grid can supply to the facilities of the engineering faculty of the Technical University of Cotopaxi, with the purpose of reducing the billing of the electric service. In the study the global radiation was collected for the period of one year, data that analyzed statistically through the frequency histograms to determine the solar potential of the institution, whose highest average irradiation was presented in November with a value of 5.4 kWh/(m2 ∙ day) and maximum irradiance of 931 W/m2 at 1:00 pm, information used in the design of the photovoltaic system connected to the grid, in order to ensure self-consumption of energy in the building of the faculty of engineering and applied sciences, when it is in its normal operation. The weekly demand for the facilities of the faculty of engineering was estimated with the Fluke 435 series II Analyzer, which recorded a maximum average power of 35.11 kW on Wednesday at 18:00 h. In addition, at 1:00 p.m. on Thursday where the highest irradiance was found, it measured an average value of 29.88 kW. The photovoltaic generator has 66 solar panels, whose installed capacity is 26.4 kW divided into two groups: 14.4 kW and 12 kW, respectively located on the roof of the building in a free area of 573.47 m2. In this way, the system annually could deliver 30336 kWh to the institution, at the same time; avoid the emission of 18.42 tons of CO2 per year.